The association between clinical periodontal parameters and free haem concentration within the gingival crevicular fluid: a pilot study. (11th June 2015) - Liu, L. Y.; McGregor, N.; Wong, B. K. J.; Butt, H.; Darby, I. B.
Abstract : Objectives: To investigate the concentration of local free haem in gingival crevicular fluid at periodontally healthy compared with diseased sites in relation to clinical periodontal parameters. The second objective is to investigate for any correlation between smoking and haem concentration. Material and Methods: Clinical parameters were recorded for two healthy and two diseased sites from 22 patients with untreated periodontitis. Gingival crevicular fluid samples were collected from the same sites. Haem assay analysis was undertaken to determine haem concentration at these sites. Results: Gingival crevicular fluid haem concentration was higher at periodontally diseased sites compared to healthy sites (mean 46.6 ± 70.6 nm in healthy vs. 1116.6 ± 2007.0 nm in diseased sites, p  <   0.001) and positively correlated with probing pocket depth, attachment level and radiographic bone loss. Gingival crevicular fluid haem concentration was higher in non‐smokers compared with smokers. However, no significant difference in correlation between haem concentration and clinical parameters were seen between smokers and non‐smokers ( p  >   0.3). Conclusion: The higher concentration of gingival crevicular fluid haem at diseased compared with healthy sites indicates that there is an association between increased levels of local free haem and periodontal disease. This may be through the pro‐inflammatory actions of free haem. Further study on a larger scale is required to determine the influence of smoking between haem concentration and clinical parameters.